Analysis of Inventory Management Using The Demand Driven Material Requirements Planning (DDMRP) Approach in The Fast-Food Industry - Nur Wakhid Habibullah; Vanany, Iwan (Universitas Muhammadiyah Sidoarjo, 2025)
Effective inventory management is a critical element in ensuring smooth operations and business success, particularly in the fast-food industry, which is characterized by highly dynamic demand. CV X, a fast-food company based in East Java, is currently facing challenges related to overstock and stockout conditions that hinder operational efficiency. Additionally, limited cold storage capacity further complicates efforts to maintain inventory balance amidst fluctuating demand. As the industry shifts from a push-based to a pull-based system—prioritizing flexibility and responsiveness in meeting customer demand—an adaptive inventory management approach becomes essential. This study analyzes the inventory management system at CV X using the Demand-Driven Material Requirements Planning (DDMRP) method to address overstock and stockout issues. DDMRP is chosen due to its ability to integrate dynamic buffer stock control and inventory adjustments based on real-time demand signals, enabling a more responsive supply chain while optimizing the use of limited cold storage capacity. This research employs secondary data from CV X for the year 2023, including production, sales, and inventory records, analyzed using descriptive and quantitative methods. The results indicate that the implementation of DDMRP successfully reduced the average inventory level by 6.62%, decreased overstock by 96.29%, and lowered stockout occurrences by 88.51%.